Procyanidins can interact with Caco-2 cell membrane lipid rafts: involvement of cholesterol - Verstraeten, Sandra Viviana (2013)
Large procyanidins (more than three subunits) are not absorbed at the gastrointestinal tract but could exert local effects through their interactions with membranes. We previously showed that hexameric procyanidins (Hex), although not entering cells, interact with membranes modulating cell signaling and fate. This paper investigated if Hex, as an example of large procyanidins, can selectively interact with lipid rafts which could in part explain its biological actions. This mechanism was studied in both synthetic membranes (liposomes) and Caco-2 cells. Hex promoted Caco-2 cell membrane rigidification and dehydration, effects that were abolished upon cholesterol depletion with methyl-β-cyclodextrin (MCD). Hex prevented lipid raft structure disruption induced by cholesterol depletion/redistribution by MCD or sodium deoxycholate. Supporting the involvement of cholesterol–Hex bonding in Hex interaction with lipid rafts, the absence of cholesterol markedly decreased the capacity of Hex to prevent deoxycholate- and Triton X-100-mediated disruption of lipid raft-like liposomes. Stressing the functional relevance of this interaction, Hex mitigated lipid raft-associated activation of the extracellular signal-regulated kinases (ERK) 1/2. Results support the capacity of a large procyanidin (Hex) to interact with membrane lipid rafts mainly through Hex–cholesterol bondings. Procyanidin–lipid raft interactions can in part explain the capacity of large procyanidins to modulate cell physiology.